2022
DOI: 10.1093/petrology/egac091
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Hawaiian Volcano Magmatic Plumbing System and Implications for Melt/Edifice and Melt/Lithosphere Interaction: Constraints from Hualālai Xenoliths

Abstract: The evolution of Hawaiian magmatic storage and transport systems in response to variations in magma supply over the course of volcano lifespan can have a significant influence on the type and amount of wallrock material that is assimilated by ponded melts prior to eruption. Understanding this plumbing evolution is therefore critical for evaluating the extent to which such melt/wallrock interaction affects the geochemical signals of Hawaiian basalts. We have examined mineral major and trace element and Sr-Nd-Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Based on rare earth element signatures in these pyroxenes (elevated LREE contents relative to MREE and HREE contents) the authors concluded that the anomalously high pressure estimates of the wehrlitic clinopyroxene crystals result from chemical modification of Na 2 O (and REE) by reactive porous flow in olivine ±clinopyroxene mush zones. Comparison with other thermobarometric techniques (E.g., Opx-Cpx, melt inclusions, Gao et al, 2022, as well as identifying trace element patterns indicative of reactive flow, provide one method to interpret the spuriously high pressure estimates returned from these cumulate Cpx.…”
Section: Cpx-liq and Cpx-only Pressures Calculating Using Pec-correct...mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on rare earth element signatures in these pyroxenes (elevated LREE contents relative to MREE and HREE contents) the authors concluded that the anomalously high pressure estimates of the wehrlitic clinopyroxene crystals result from chemical modification of Na 2 O (and REE) by reactive porous flow in olivine ±clinopyroxene mush zones. Comparison with other thermobarometric techniques (E.g., Opx-Cpx, melt inclusions, Gao et al, 2022, as well as identifying trace element patterns indicative of reactive flow, provide one method to interpret the spuriously high pressure estimates returned from these cumulate Cpx.…”
Section: Cpx-liq and Cpx-only Pressures Calculating Using Pec-correct...mentioning
confidence: 99%
“…Opx-Liq and Cpx-Liq thermobarometry). Opx-Cpx thermobarometry can also be applied in systems where it is difficult to analyse the composition of the liquid (e.g., highly crystalline lavas or xenoliths, Gao et al, 2022;.…”
Section: Two Pyroxene (Cpx-opx) Thermobarometrymentioning
confidence: 99%